Neurexin 1 (NRXN1) Splice Isoform Expression During Human Neocortical Development and Aging - Jenkins, Aaron K. (Mol Psychiatry, 2015)
Neurexin 1 (NRXN1), a presynaptic adhesion molecule, is implicated in several neurodevelopmental disorders characterized by synaptic dysfunction including, autism, intellectual disability, and schizophrenia. To gain insight into NRXN1’s involvement in human cortical development we used quantitative real time PCR to examine the expression trajectories of NRXN1, and its predominant isoforms NRXN1-α and NRXN1-β in prefrontal cortex from fetal stages to aging. Additionally, we investigated whether prefrontal cortical expression levels of NRXN1 transcripts are altered in schizophrenia or bipolar disorder in comparison to non-psychiatric control subjects. We observed that all three NRXN1 transcripts were highly expressed during human fetal cortical development, dramatically increasing with gestational age. In the postnatal DLPFC, expression levels were negatively correlated with age, peaking at birth until approximately 3 years of age, after which levels declined dramatically to be stable across the lifespan. NRXN1-β expression was modestly but significantly elevated in the brains of patients with schizophrenia compared to non-psychiatric controls, whereas NRXN1-α expression was increased in bipolar disorder. These data provide novel evidence that NRXN1 expression is highest in human prefrontal cortex during critical developmental windows relevant to the onset and diagnosis of a range of neurodevelopmental disorders, and that NRXN1 expression may be differentially altered in neuropsychiatric disorders.